Comparison between Real-Time Quantitative PCR Detection of HER2 mRNA Copy Number in Peripheral Blood and ELISA of Serum HER2 Protein for Determining HER2 Status in Breast Cancer Patients - Maria Savino; Paola Parrella; Massimiliano Copetti; Raffaela Barbano; Roberto Murgo; Vito Michele Fazio; Vanna Maria Valori; Massimo Carella; Maria Garrubba; Stefano Angelo Santini (Cellular Oncology)
Background: The development of non-invasive procedure to determine HER2 status may represent a powerful method for monitoring disease progression and response to the treatment.